Predictive characteristics of male fertility in alpacas with special reference to seminal NGF - Carrasco, R. A. (2023)
Recent studies document the LH-releasing pathway of nerve growth factor (NGF) in male camelids and that the LH response to seminal NGF is associated with elevated plasma testosterone concentration. Results provide rationale for the hypothesis that NGF in semen is associated with male fertility. In Experiment 1, the association between the amount of NGF in the ejaculate and characteristics of the male reproductive system was examined in alpacas. The concentration of NGF was measured by radioimmunoassay in semen samples collected from male alpacas (n = 47) and correlated with sperm morphology and motility, and measurements of the male reproductive anatomy. Most ejaculates had NGF concentrations that, based on previous studies, triggered ovulation in female camelids, however, we only found a positive correlation between NGF concentration with sperm concentration, thread formation and total NGF, and a negative correlation with pH. In Experiment 2, a retrospective analysis was carried out to determine if breeding performance during the previous season was related to recent concentrations of seminal NGF in male alpacas (n = 22). Birth rates tended to be correlated with sperm concentration and total amount of NGF in the ejaculate (P = 0.09). Experiment 3 was a prospective study to determine the relationship between seminal NGF (n = 8 male alpacas) and ovulation and pregnancy rates in a breeding trial. No association was detected between seminal NGF concentration and ovulation rate, pregnancy rate, or LH response in the female. We conclude that among the breeding males used in our study, the abundance of seminal NGF was correlated with sperm concentration and thread formation, however, it was not predictive of male fertility in alpacas. Examination of males not previously selected as breeding stock may be expected to include a broader range of seminal NGF and provide a more comprehensive understanding of the relationship between seminal NGF and male fertility.